2016
DOI: 10.1039/c6ra10933k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surfactants and their concentration on the liquid exfoliation of graphene

Abstract: We investigated the effect of surfactants and their concentration (C sur ) on the final graphene concentration (C G ) via the liquid-phase exfoliation method. Six typical surfactants including ionic and non-ionic ones were explored and the optimized C sur for each surfactant was suggested. For ionic surfactants, C G increases with C sur before reaching its maximum and then maintains the high level. The different mechanisms of ionic and non-ionic surfactants in stabilizing graphene dispersions are explained by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 54 publications
6
52
0
Order By: Relevance
“…34 A subsequent study demonstrated that the lowest concentration of SDBS allowing the exfoliation and stabilization of graphene in water was equal to 0.05 mg mL −1 . 35 Anyway, since in our model GBMs were topically applied on the RhE surface as powder, stable water dispersion of these materials did not represent a limitation. For this reason, to demonstrate the role of surfactant residues in the irritation potential of FLG-SDS and FLG-SDBS, as a final step of the study both materials were further washed after the exfoliation process to reduce the amount of surfactants (0.22% and 1.90%, respectively).…”
Section: Papermentioning
confidence: 99%
“…34 A subsequent study demonstrated that the lowest concentration of SDBS allowing the exfoliation and stabilization of graphene in water was equal to 0.05 mg mL −1 . 35 Anyway, since in our model GBMs were topically applied on the RhE surface as powder, stable water dispersion of these materials did not represent a limitation. For this reason, to demonstrate the role of surfactant residues in the irritation potential of FLG-SDS and FLG-SDBS, as a final step of the study both materials were further washed after the exfoliation process to reduce the amount of surfactants (0.22% and 1.90%, respectively).…”
Section: Papermentioning
confidence: 99%
“…From a general viewpoint, gradually increasing the concentration of surfactant led to modest increases in the electrical conductivities. Again reiterating the importance of surfactant concentration in exfoliation and keeping the exfoliated layer stably dispersed (Lotya et al, 2009;Mohamed et al, 2018;Suriani, Nurhafizah, Mohamed, Zainol, & Masrom, 2015;Wang, Yi, & Shen, 2016). It was hypothesized that the chosen surfactant concentrations (0.05 -0.1 M) are sufficient to form a network that provides electrical pathways, considering the significant σ from neat cellulose, and that the presence of RGO enveloping the cellulose network did assist the development of the electrical conductivity of the paper.…”
Section: Zeta Potential Measurementsmentioning
confidence: 99%
“…However, that is not always the case, for example with TC3Ph3-AN. The same kind of behavior was also experienced with TC3Ph3, again illustrating that surfactants may cease to "perform" at a certain limit [25,26]. It is clear that aromatization of the headgroups enhances graphenecompatibility compared with the normal sodium surfactants.…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 57%
“…Returning to Table 2, the changes in electrical conductivity are broadly consistent with increasing surfactant concentration [15,25]. However, that is not always the case, for example with TC3Ph3-AN.…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 71%